Desain Arsitektur Jaringan IoT Terintegrasi pada Smart Campus Universitas Bumigora Menggunakan VLAN untuk Ruang Kelas Cerdas - Zul Fahmi, Muhammad Farhan; Tabroni, Rizal; Muhammad, Fhadilla; Husain (CORISINDO 2025, 2025)
The application of Internet of Things (IoT) technology in educational environments is expanding rapidly in response to the increasing need for energy efficiency, classroom security, and intelligent infrastructure management. This study designs a Virtual Local Area Network (VLAN)-based network architecture to integrate IoT devices such as smart lighting, automatic air conditioning, temperature sensors, access control, CCTV, and other networked equipment within smart classrooms at Universitas Bumigora, West Nusa Tenggara. The novelty of this research lies in its technical design approach, which includes per-classroom device inventory, functional VLAN segmentation, bandwidth estimation, and simulated topologies using Cisco Packet Tracer. The results demonstrate that VLAN segmentation enables structured and secure management of IoT networks, providing a practical foundation for building adaptive, modular, and scalable smart campus environments in higher education.